PENGEMBANGAN APLIKASI SIGIL SEBAGAI MEDIA PEMBELAJARAN MATERI POKOK KONSEP SIKLUS AIR DI SEKOLAH DASAR NEGERI TAPOS 02 KECAMATAN TENJO KABUPATEN BOGOR - Toharoh, Tantik; Sjaifuddin; Lukman Nulhakim (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2023)
This research was conducted based on the needs of students for a learning medium that can overcome problems during the learning process related to the difficulties of students in understanding the concept of the water cycle. The purpose of this study was to determine the response of students in the use of learning media related to the concept of the water cycle in class V science subjects SDN Tapos 02, Tenjo District, Bogor Regency. The research method used is R&D which refers to the Borg & Gall model with adjustments according to the research context at 5 stages: 1) survey and information gathering; 2) product design; 3) product validation; 4) design revisions and improvements; 5) limited trials. Data was obtained through a limited trial conducted on grade V elementary school students. The results of research on the development of the Sigil application as a learning medium show that the average percentage of student response instrument data obtained 89% of the "very good" category, thus the development of the Sigil application as a learning medium on the concept of the water cycle in grade V elementary science subjects developed by researchers is worthy of being a learning media.